ANALISIS KESALAHAN MENYAMBUNG HURUF ARAB PADA PESERTA KURSUS BAHASA ARAB DI MASJID AN NUR JAKARTA SELATAN - Ma'sum, Ali (IMTIYAZ: Jurnal Ilmu Keislaman, 2023)
Knowledge and the ability to form and connect Arabic letters are still fundamental problems among students. Several studies have shown that some of them are still wrong in connecting Arabic letters. This study aims to describe the form and level of errors of Arabic language course participants at An Nur Mosque, South Jakarta, in connecting Arabic letters. This type of research is descriptive with a qualitative approach. The research data was taken from the results of the course participant's written test and then analyzed by reducing the data, analyzing it, and then drawing conclusions. The result of the study shows that the participant's form of error connecting the Arabic letters was: Connecting letters that should be separated 2). Separating letters that should be connected 3). Forming letters not according to the rules of connecting either at the beginning, middle, or end of a word 4). Does not form a connecting line. In addition, there are 595 errors in forming and connecting letters. The highest error which 235 errors was found in the points forming letters not according to the rules of connecting either at the beginning, middle, or end of a word. Meanwhile, the lowest was 71 errors on the error points of connecting letters that should have been separated. Keywords: error; analysis; connect; Arabic; Letter